Commutators with Lipschitz Functions and Nonintegral Operators - Peizhu Xie; Ruming Gong (Journal of Applied Mathematics)
Let T be a singular nonintegral operator; that is, it does not have an integral representation by a kernel with size estimates, even rough. In this paper, we consider the boundedness of commutators with T and Lipschitz functions. Applications include spectral multipliers of self-adjoint, positive operators, Riesz transforms of second-order divergence form operators, and fractional power of elliptic operators.